PENGARUH HEDONIC SHOPPING VALUE DAN SHOPPING LIFESTYLE TERHADAP IMPULSE BUYING DENGAN POSITIVE EMOTION SEBAGAI VARIABEL INTERVENING - Fauzi, Latiffah Ulul; Welsa, Henny; Susanto, Susanto (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to determine the effect of hedonic shopping value, shopping life style on impulse buying with positive emotion as an intervening variable. , the influence of hedonic shopping value, at Matahari Departement Store Yogyakarta. This research was conducted in Yogyakrta, samples taken as many as 115 respondents with a sampling technique using accidental sampling. Data collection by distributing questionnaires using a 5-point Likert scale, to measure 19 indicators. The data collection method uses a questionnaire. For testing the instrument using the validity test and reliability test. Instrument test results, indicate that the entire instrument is valid and reliable. Data analysis using Sobel Test. The results of this study indicate that (1) Hedonic value, shopping life style has a positive and significant effect on positive emotion, (2) Hedonic value, shopping lifestyle, positive emotion has a positive and significant effect on impulse buying, (3) Positive emotion has a positive and significant effect in mediating hedonic shopping value and shopping lifestyle towards impulse buying. This shows that the variable hedonic value, shopping life style, and positive emotion affect impulse buying.